Evaluasi Kebijakan Sistem Zonasi Penerimaan Peserta Didik Baru terhadap Pemerataan Akses Pendidikan Berkualitas: Studi Kepustakaan - Fitria Ningsih; Ninik Upriani; Jalaludin Jalaludin (Perhimpunan Sarjana Ekonomi dan Bisnis, 2026)
The zoning system policy in New Student Admission represents a strategic effort by the Indonesian government to achieve equitable access to quality education. This research aims to analyze the implementation of the zoning system policy in student admission, identify supporting and inhibiting factors, and evaluate its impact on educational quality equity across schools and regions. The method employed is library research with a qualitative approach, analyzing official policy documents, accredited scientific journals, and research findings from the 2021-2024 period. Data analysis was conducted through content analysis techniques encompassing reduction, data presentation, and conclusion drawing. Research findings indicate that zoning system implementation has enhanced educational accessibility by prioritizing students based on geographical proximity, yet faces various challenges including uneven school distribution, facility quality disparities, teacher distribution inequality, and administrative complications. Positive impacts of this policy include improved access to nearby schools and opportunities for students from economically disadvantaged families, while negative impacts encompass student difficulties in choosing preferred schools and incomplete achievement of learning quality equity. Research findings suggest that the zoning system has not been fully effective in realizing educational quality equity due to persistent infrastructure disparities and community perceptions toward favored schools. Infrastructure improvements, quality teacher redistribution, policy adjustments aligned with local conditions, intensive socialization, periodic evaluation, and strengthened affirmative policies are necessary to enhance zoning system effectiveness.